El banco de datos ‘Hesperia’ (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
‘Hesperia’ is an interuniversitary project consisting of a computerized databank which includes all the linguistic evidence related to the Iberian Peninsula in Antiquity. Its logical and physical supports are described in this paper, as well as its searching engine and the six databases (respectively devoted to Palaeohispanic inscriptions and coin legends, names, lexicon, bibliography, cartography and numismatics) of which ‘Hesperia’ is made up.
Keywords: Online databank; Palaeohispanic languages; Epigraphy; Onomastics; mapserver; lexicon; coin legends